Justice in the Perspective of the Qur'an and the Sacred Texts of Other Religions and its Contextuality - Hubby Dzikrillah Alfani, Ilzam; Mukhsin, Mukhsin; Sutisna, Nata (UAS PRESS, 2024)
This paper explores the views of various religions on justice as a value that must be upheld because it pertains to the well-being of life. The purpose is to broaden the understanding of interfaith ideologies in Indonesia. This research employs a qualitative approach, relying on literature studies analyzed descriptively. The paper concludes that there are several perspectives on the definition of justice. According to Islam, justice is divided into three forms: first, justice in a material and immaterial sense, closely related to fulfilling rights and obligations among all beings. Second, justice in the form of balance, meaning impartiality towards oneself, relatives, and those of the same faith. Third, justice as retribution, signifying the consequences of one's actions. In Christianity, the term